Untangling the Amorimia rigida complex, a puzzling group of lianescent Malpighiaceae from Eastern Brazil - de Almeida, Rafael Felipe; van Den Berg, Cássio; Amorim, André Márcio Araujo (Phytotaxa, 2016)
A proposal for the resolution of the Amorimia rigida complex is presented, including a new combination, three new species, and the redescription of A. rigida and A. velutina. The newly described and the re-established taxa are endemic to Eastern Brazil, and can be differentiated from A. rigida s.s. by details in the leaves, indumenta, floral, and fruit morphology. This study includes morphological descriptions for all taxa, along with an identification key, illustrations, a distribution map, conservation assessments, comments on ecology, nomenclature, and taxonomy, and a table comparing all species belonging to this complex.